Biographical fiction a reader - Lackey, Michael (Bloomsbury Academic, 2017)
In Biographical Fiction: A Reader, some of the finest scholars and writers of biofiction clarify what led to the rise of this genre, reflect on its nature and form, and specify what it is uniquely capable of doing.